Global burden and future projections of geriatric gout (1990–2021): a comprehensive analysis and Bayesian Age-Period-Cohort modeling - Jiqing Wang; Yonghui Zhao; Boya Zhao; Yingang Zhang (Frontiers in Public Health)
IntroductionGout is increasingly recognized as a major chronic condition among older adults, contributing significantly to global disease burden, healthcare costs, and disability.MethodsThis study utilized data from the Global Burden of Disease (GBD) database, covering 204 countries and regions from 1990 to 2021. We evaluated age-standardized incidence rates, prevalence, and Years Lived with Disability (YLDs) of gout among individuals aged 60 years and older. Inequality and frontier analyses were conducted to explore disparities, and Bayesian Age-Period-Cohort (BAPC) models were applied for future trend projections up to 2036.ResultsAll indicators—incidence, prevalence, and YLDs—showed a steady increase across the study period, with particularly rapid growth observed in high Socio-demographic Index (SDI) regions and among older women. Although the burden was concentrated in high SDI countries, increasing trends were also evident in low SDI areas. Significant heterogeneity was found among countries with similar SDI levels.DiscussionThe projected rise in gout burden through 2036 underscores the urgent need for targeted public health strategies. Disparities across SDI groups suggest that medical infrastructure, prevention programs, and cultural contexts play critical roles in disease control. Comprehensive interventions are essential to manage this growing challenge, especially among high-risk older populations.